The Quest for Stability: The Macro View - Willem H. Buiter; Stefan Gerlach; Clemens J.M. Kool; José Vi\~nals (SUERF - The European Money and Finance Forum, 2010)
On September 3-4, 2009 SUERF and Utrecht University School of Economicsorganized the Colloquium "The Quest for Stability" in Utrecht, the Netherlands. The papers included in this SUERF Study are based on contributions to the Colloquium.
Keywords: E4; E41; E42; E43; E44; E5; E52; E58; F31; F33; F34; F41; F42; 330; asset prices; bubbles; financial institutions; global recession; interest rates; liquidity; monetary policy; regulation; stability; supervision